2006 IFIP International Conference on Very Large Scale Integration 2006
DOI: 10.1109/vlsisoc.2006.313238
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of an HDTV Intraframe Predictor for a H.264 Decoder

Abstract: Multimedia applications need larger and larger bandwidth. The only way to face these demands is to provide more efficient compression algorithms, with the expense of computational complexity. The most efficient compression standard available today is the H.264/AVC. On the architectural point of view, an H.264 decoder can be seen as a system of six main modules: entropy decoder, inverse quantization, inverse transform, motion compensation, intraframe prediction and deblocking filter. These modules can be design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…From Table 2, the proposed design noted 21% increase in throughput while using only 48% of LUT resources as reported by [5]. The design in [7] supports 1080p HD at 30 fps using 7K LUT resources, three times more than used by our design.…”
Section: B Area Computationsupporting
confidence: 57%
See 2 more Smart Citations
“…From Table 2, the proposed design noted 21% increase in throughput while using only 48% of LUT resources as reported by [5]. The design in [7] supports 1080p HD at 30 fps using 7K LUT resources, three times more than used by our design.…”
Section: B Area Computationsupporting
confidence: 57%
“…The paper decodes 640x480 resolution H.264 video at 27 fps. Architecture in [5] utilizes separate local memory for storage, causing inefficient usage of on-chip memory. It does not reuse similar functional blocks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The base architecture of our intra prediction circuit is the one described in [2]. As illustrated in Fig.…”
Section: Overall Intra Prediction Circuitmentioning
confidence: 99%
“…2 (a). We further investigated each prediction mode and found that some of the computations can be expressed by the following simpler equation: We propose to use another common computation unit to implement the function described by Equation (2). As shown in Fig.…”
Section: Common Computation Units and Common Registersmentioning
confidence: 99%